DEVELOPMENT OF LEATHER CALLIGRAPHY CRAFTS THROUGH INNOVATION OF DESIGN AND COLORING TECHNIQUE - Adam Wahida; Sigit Purnomo Adi (Proceeding of International Conference on Art, Language, and Culture, 2017)
This article is the result of community service program to develop micro business of leather calligraphy crafts in Sonorejo Village Sukoharjo District. So far the product of leather calligraphy, made using a single color screen printing technique with a monotonous visual form without variations of decoration. In general, craftsmen tend to be passive in developing new designs because they feel enough to produce calligraphy from the order designs carried by middlemen. Dependence on the middleman, causing the weak bargaining position of craftsmen in determining the price of the product. Meanwhile, craftsmen have production experience as a basis to develop their creativity in creating design innovations that are likely to expand the marketing area. In view of these conditions, the program is implemented to develop creativity and craftsman skills in: 1) create more varied designs of calligraphy, 2) create decorative patterns, 3) apply techniques of color screen printing on leather calligraphy crafts products. This community service program uses a participatory approach with a buttom up method; where the participation of craftsmen during the activity is expected to be able to answer their needs in a participative manner. Its activities are focused on training on the development of shape design, decorative pattern, and application of color screen printing technique. Through this program, there has been an increase in the ability of craftsmen in terms of: 1) creating new and more varied calligraphic designs using coreldraw software. 2) composing calligraphy style, decorative pattern, and background in harmony and artistic, 3) creating product according to design by applying color screen printing technique.